(untitled) (International Journal of Engineering and Computer Science, 2018)
Hybridization of Rough Sets with intuitionistic fuzzy sets is commonly in use for deriving several real time applications. In this aspect, we describe three types of algorithms namely lower, upper and rough indexing algorithms to index the records of decision table with intuitionistic fuzzy decision attributes and the same are implemented using C Programming.